Meninjau Ulang Ketentuan Presidential Threshold dalam Pemilihan Presiden dan Wakil Presiden di Indonesia - Aprilian Sumodiningrat (Jurnal Kajian Pembaruan Hukum, 2021)
The presidential threshold is a requirement for the nomination of the President and Vice President to meet the minimum threshold percentage for support from the DPR or the number of valid national votes. Presidential threshold provisions are contained in various laws and regulations regarding Elections. This research is juridical study using a conceptual approach and statute approach. The legal materials used in this research are primary and secondary legal materials. The two legal materials are inventoried; then used as a basis for compiling a prescriptive study of the legal issues raised. The results of this study state that the presidential threshold has started since 2004. Regulations regarding post-reform elections always include a presidential threshold. Then, the presidential threshold has been 'tested' several times by the Constitutional Court. Various decisions of the Constitutional Court stated that the presidential threshold is one of the provisions which is the domain of open legal policy for legislators or the making of laws. Furthermore, the implication of the presidential threshold is aimed at simplifying the fragmentation of political parties in parliament. The nominations for the President and Vice President promoted by the parliamentary political party actually allow for more than two candidates; and it is also possible to have an Election that does not get the support of more than 50 persen of the voters' vote. Thus, effectiveness is needed regarding the implementation of the presidential threshold provisions in the presidential system by strengthening relations between presidential institutional actors and the President's non-institutional personnel. KEYWORDS: Presidential Threshold, General Election, Open Legal Policy.